A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary - Ripka, Géza (Zootaxa, 2016)
A new species of eriophyoid mite, Aceria wassalberti n. sp. associated with Minuartia frutescens (Caryophyllaceae), is described and illustrated from Hungary. A key to the Aceria species known on Caryophyllaceae is given. Remarks are provided on the eriophyoid mites currently known from caryophyllaceous host plants.